Contribution of the Roman rat lines/strains to personality neuroscience: neurobehavioral modeling of internalizing/externalizing psychopathologies - Alberto Fernández-Teruel; Toni Cañete; Daniel Sampedro-Viana; Ignasi Oliveras; Rafael Torrubia; Adolf Tobeña (Personality Neuroscience, 2023)
The Roman high-avoidance (RHA) and low-avoidance (RLA) rat lines/strains were established in Rome through bidirectional selection of Wistar rats for rapid (RHA) or extremely poor (RLA) acquisition of a two-way active avoidance task. Relative to RHAs, RLA rats exhibit enhanced threat sensitivity, anxiety, fear and vulnerability to stress, a passive coping style and increased sensitivity to frustration. Thus, RLA rats’ phenotypic profile falls well within the “internalizing” behavior spectrum. Compared with RLAs and other rat strains/stocks, RHAs present increased impulsivity and reward sensitivity, deficits in social behavior and attentional/cognitive processes, novelty-induced hyper-locomotion and vulnerability to psychostimulant sensitization and drug addiction. Thus, RHA rats’ phenotypes are consistent with a “disinhibiting externalizing” profile. Many neurobiological/molecular traits differentiate both rat lines/strains. For example, relative to RLA rats, RHAs exhibit decreased function of the prefrontal cortex (PFC), hippocampus and amygdala, increased functional tone of the mesolimbic dopamine system, a deficit of central metabotropic glutamate-2 (mGlu2) receptors, increased density of serotonin 5-HT2A receptors in the PFC, impairment of GABAergic transmission in the PFC, alterations of several synaptic markers and increased density of pyramidal immature dendrític spines in the PFC. These characteristics suggest an immature brain of RHA rats and are reminiscent of schizophrenia features like hypofrontality and disruption of the excitation/inhibition cortical balance. We review evidence supporting RLA rats as a valid model of anxiety/fear, stress and frustration vulnerability, whereas RHA rats represent a promising translational model of neurodevelopmental alterations related to impulsivity, schizophrenia-relevant features and comorbidity with drug addiction vulnerability.